Internet, Media Usage, and Poverty: Quadrant Mapping of ICT Trend and Poverty Level in Indonesia - Hastjarjo, Sri; Wahyunengseh, Rutiana Dwi (Universitas Semarang, 2024)
Introduction: This article addressed the research problem: 'how the information and communication technology usage related to the poverty rate in Indonesia in 2020-2021, compared between provinces and rural-urban segmentation.’ This study contributed evidences for the development of digital literacy policies to answer previous research debates on the extent to which information and communication technology is a useful tool for reducing poverty, which is one of the Sustainable Development Goals. Methods: Using a quantitative approach, this study used the data from the Indonesian Central Bureau of Statistics. Data is analyzed using product moment correlation to determine the relationship between information and communication technology penetration and the poverty rate, the results then are displayed using quadrant mapping. Findings: This study found variations in relations between provinces and rural-urban segmentations. High internet penetration and media use are not always accompanied by a low poverty index. In conclusion, the expansion of internet needs to be complemented by massive and systematic digital literacy education in order to effectively accelerate poverty reduction. Originality: This study meets the need for novelty as the issue discussed is related to poverty and information and communication technology penetration using spatial analysis. The novelty can be seen from the result of bibliometric analysis.